Tamamlayıcı ve alternatif sağlık yaklaşımlarının gebelikte kullanımı - Kılavuz, Mustafa (İstanbul Medipol Üniversitesi Sağlık Bilimleri Enstitüsü, 2017)
Modern tıp tedavilerinden farklı olarak tamamlayıcı ve alternatif sağlık yaklaşımları kullanımı dünyada giderek daha da yaygın hale gelmeye başlamıştır. Bu araştırma amacı; Gebelik döneminde tamamlayıcı ve alternatif sağlık yaklaşımlarının kadınlar tarafından kullanımının belirlenmesidir. Araştırmanın evrenini İstanbul'da bir eğitim araştırma hastanesine başvuran gebeler oluşturmaktadır. Araştırma verileri Aralık 2016-Şubat 2017 tarihleri arasında gebe polikliniğine başvuran ve gebeliği 25'inci haftayı geçen kadınlardan toplanmıştır. Araştırmaya katılan gebeler en çok %96.3'ü bitkileri, %92.3'ü duayı, %88.9'u vitaminleri, %85.7'i masajı, %74.2'si hidroterapi/kaplıca yöntemini bilmektedir. Gebelerin %82.3'ü bitkileri, %81.4'ü duayı, %68.3'ü vitaminleri, %45.1'i masajı, % 3.,6'sı aromaterapi yöntemini kullanmaktadır. Araştırmaya katılan gebelerin, eğitim düzeyleri, çalışmaları ve gelir düzeyleri arttıkça sağlık yaklaşımlarını bilme ve kullanma oranları artmaktadır. Tamamlayıcı ve alternatif sağlık yaklaşımları kullanmak isteyen gebelere bu konu hakkında bilgi verilmeli, gebeye en uygun yaklaşım bir kadın doğum hemşiresi ile birlikte seçilmelidir.

Complementary and alternative health approaches have been become most popular than modern medicine in these days. To purpose of this research is to determine complementary and alternative health approaches during pregnancy by women. The study was performed on pregnant women who consulted to the training and research hospital in İstanbul. The data was collected from over 25 weeks pregnant women who consulted to policlinic between December 2016 and February, 2017. 96.3% of pregnant women who were joined the study knew phytotherapy, 92.3% of the women know praying method, 88.9% know vitamins, 85.7% know massage and 74.2% of this women know hydrotherapy/spa method. However 82.3%, of this women had performed phytotherapy, 81.4% had performed praying method, 68.3% had used vitamins, 45.1% had performed massage and 32.6% of this women had used aromatherapy method. When education level, working and income rate of pregnant women increase, rate of being aware of health approaches and usage of these approaches become more increased. Information about utilization of complementary and alternative health approaches should be given to pregnant women who want to utilize them and best approaches method for pregnant women should be chosen by gynecology nurse.
Utilazition of complementary and alternative health approaches for pregnancy
Keywords: Alternative Medicine; Complementary Medicine; Complementary Therapies; Alternative Medicine; Complementary Medicine; Complementary Therapies